2020
DOI: 10.1080/14778238.2020.1838962
|View full text |Cite
|
Sign up to set email alerts
|

The role of organisation structure in the success of start-up science and technology parks (STPs)

Abstract: Early stage start-up STPs, have a central initiative controlling the decisionmaking. In early maturity, better decision-making is required and decisions are best taken with the input of optimally two on-cluster firms; this ambidextrous situation is superior under all circumstances. Where poor-fit innovations abound and where the STP has been unable to attract large firms, retaining a hierarchical decision process is most helpful, even when the quality of decisionmaking is poor. This developmental trajectory wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…As an STP grows, poor decisions will inevitably become more and more costly, and to avoid a market failure (see Figure 2) may force a high-tech STP to re-focus into a lower-tech area, e.g., hosting general businesses, incubator services, etc. [34]. The alternative route, the other branch of the 'Y-shaped path', is where decision-making can be strengthened within 20 years of STP founding, by including experienced managers from larger firms who possess relevant in-depth knowledge [35].…”
Section: Early Stagesmentioning
confidence: 99%
See 2 more Smart Citations
“…As an STP grows, poor decisions will inevitably become more and more costly, and to avoid a market failure (see Figure 2) may force a high-tech STP to re-focus into a lower-tech area, e.g., hosting general businesses, incubator services, etc. [34]. The alternative route, the other branch of the 'Y-shaped path', is where decision-making can be strengthened within 20 years of STP founding, by including experienced managers from larger firms who possess relevant in-depth knowledge [35].…”
Section: Early Stagesmentioning
confidence: 99%
“…To do this, the young STP should become a focus of innovation that can attract larger firms interested in new ideas, fresh talent and take-overs [36]. There is a trade-off between improved decision-making and the transaction costs incurred for the improvement, which occurs when decision makers from two large organizations are included in the process [34]; although more than two large firms may be present in the STP, involving more large firms simply increases the transaction costs. This scenario was checked by [37], who compared STPs with zero or two large firms in residence, finding support in that the employment rates amongst on-cluster firms in the STP when two large firms were present were significantly better than in the case when no large firms were present, using off-cluster employment as a control [37].…”
Section: Early Stagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors identify more directly the critical success factors for STPs (Berbegal-Mirabent et al, 2020;Cabral, 1998;5 Etzkowitz & Zhou, 2018;Khanmirzaee et al, 2021;Koh et al, 2005;Xie et al, 2018;Yang, 2018) or focus on STP business model and strategy (Bozzo, 1998;Durão et al, 2005;Hansson et al, 2005). Some recent papers emphasise best management practices (Al-Kfairy & Mellor, 2020;Durak et al, 2021;Laspia et al, 2021;Magalhães Correia et al, 2021) and the role played by tenant expectations and how STPs can modulate them (Lecluyse & Knockaert, 2020;Ng et al, 2021).…”
Section: Main Topics Analysedmentioning
confidence: 99%
“…Moreover, Albahari et al (2018) argued the positive effect of STPs on firms' innovation performance. However, according to Khanmirzaee et al (2018) and Al-Kfairy and Mellor (2020), empirical studies on the evaluation of STP performance of STPs found little evidence supporting these benefits. Despite the lack of empirical support in favor of policy benefits associated with STPs, the idea of STPs is yet popular and persistently used as a policy measure to promote innovation and knowledge sharing.…”
Section: Introductionmentioning
confidence: 99%